PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PETA BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SDN MUNGGUT 03.: Penerapan model pembelajaran - arifati mungfarida; Suyanti; Dian Eky Nur Antika Hastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of students in science learning, especially in the material My Indonesia is Rich in Culture. This study aims to improve the learning outcomes of fourth grade students of SDN Munggut 03 in the material My Indonesia is Rich in Culture by using the Problem Based Learning (PBL) Model assisted by Cultural Map Media. This study uses the Classroom Action Research (CAR) method and the research subjects are fourth grade students of SDN Munggut 03. This research was conducted in two cycles. Based on data analysis techniques through observation, tests and documentation obtained from the results of the second cycle of research, it has shown that there is an increase in science learning outcomes with a percentage of completion of 93.33%. This shows that the application of the Problem Based Learning model assisted by Cultural Map media can improve science learning outcomes in fourth grade students.